Interactive Support in The Tambak Wedi Village Area of Surabaya City to Avoid Stunting - museyaroh, museyaroh; Christyaningsih, Juliana; Nur Kholifah, Siti; Ariyanti, Ida; Retno Puspitadewi, Teresia; Suyanto, Beny; Hindaryani, Nurul; Rahmawati, Laili (Frontiers in Community Service and Empowerment, 2024)
ABSTRACT Stunting remains a serious challenge for Indonesian society. The 2018 basic health research reported that the prevalence of stunting among toddlers reached 30.8%. The impact of stunting is not only on physical growth but also on cognitive development and the risk of diseases in adulthood. Community service plays a crucial role in supporting government efforts to address stunting through nutrition education, infant and child feeding practices, sanitation, hygiene, and family economic empowerment. Based on this, the involvement of higher education institutions is necessary to improve public health through an approach of interprofessional collaboration and interprofessional education designed in community service activities that focus on empowering communities through integrative assistance. This community service is carried out in 2024, located in Tambak Wedi Village, Surabaya. The activities conducted include training and assistance in the production of processed foods based on moringa leaves and fish, health education on healthy living behaviors, guidance on parenting and breastfeeding/MPASI, training for early detection of high-risk pregnancies for families, and checking hemoglobin and protein levels for pregnant women in a state of chronic energy deficiency who receive supplementary feeding based on moringa leaves and fish. At the beginning of the community service activities, the results of health and laboratory examinations were as follows: several mothers were found to have a mid-upper arm circumference (MUAC) below 23.5 cm, which may indicate a risk of chronic energy deficiency (CED). Pregnant women were still found with hemoglobin levels below 11 g/dL, indicating anemia during pregnancy. Additionally, protein levels in pregnant women were found to be 6.2 g/dL, and there was one stunted child and seven children in a pre-stunting condition. Following up on the results of the initial health examination, interventions were carried out for pregnant women with chronic energy deficiency and toddlers at risk of stunting by providing snacks made from moringa and fish for two weeks. The Surabaya Hebat cadres also received a refresher on early detection screening for high-risk pregnant women INDEX TERMS Stunting, Moringa leaves and fish, Tambak Wedi